A mobilities perspective on migration in the context of environmental change. (24th July 2019) - Wiegel, Hanne; Boas, Ingrid; Warner, Jeroen
Abstract: Academic, political, and policy debates about the connection between environmental change and human migration have long focused on migration drivers and outcomes, resulting in a limited discussion between the discourses of "desolate climate refugees" and "environmental migrants as agents of adaptation." These perspectives remain dominant, particularly in policy and media circles, despite academic critique and the recent emergence of more diverse approaches. In this intervention, we contribute to the recent turn in environmental migration research by seeking to better ground and pluralize our understanding of how environmental change and human mobility relate. We do so by offering a mobilities perspective that centers on the practices, motives, and experiences of mobility and immobility in the context of environmental change: When and why do people decide to move—or not to move—in response to environmental changes? How do they cope with migration pressures? Where do they move, under what conditions, and who can or must stay behind? This approach attends to the diverse aspirations and differential capabilities that underlie particular practices of movement or nonmovement, reflecting both individual characteristics as well as interconnections with uneven power relations across local, regional, and global scales. A mobilities approach offers a starting point for an expanded research agenda on environmental im/mobilities. This enables academic analysis and policy discussion of the human (im)mobility‐environmental change nexus to become better attuned to the actual practice and heterogeneous needs of those affected. This article is categorized under: Climate and Development > Social Justice and the Politics of Development Vulnerability and Adaptation to Climate Change > Values‐Based Approach to Vulnerability and Adaptation Abstract : This coastal community in Bangladesh is affected by daily tidal inflow. Several families have moved, while others remain. Understanding dynamics between mobility and immobility in the context of environmental changes requires a mobilities approach offering a grounded perspective of the daily practices of movement.